2020
DOI: 10.2147/ott.s227467
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-31 Modulates Liver Cancer HepG2 Cell Apoptosis and Invasion via ROCK1/F-Actin Pathways</p>

Abstract: Purpose: Liver cancer is one of the most common malignant tumor in the world. miR-31 is downregulated in liver cancer and associated with tumor growth and metastasis. However, the underlying mechanism remains unclear. Methods: Cellular apoptosis was detected via MTT, TUNEL assay, LDH release and Annexin V/PI flow-cytometry analysis. Cellular migration and invasion were measured by the Transwell chamber assay. Mitochondrial functions were evaluated via mitochondrial membrane potential JC-1 staining and mPTP ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…We have also made some extensions to the present study. Previous studies have found that F-actin was involved in cell proliferation and motility, and its homeostasis could be regulated by ROCK1 (ROCK1 depolymerized F-actin) [38]. In the present study, ROCK1 expression was found to hamper F-actin expression, and miR-30b-3p was an upstream effector of ROCK1/F-actin.…”
Section: Discussionsupporting
confidence: 55%
“…We have also made some extensions to the present study. Previous studies have found that F-actin was involved in cell proliferation and motility, and its homeostasis could be regulated by ROCK1 (ROCK1 depolymerized F-actin) [38]. In the present study, ROCK1 expression was found to hamper F-actin expression, and miR-30b-3p was an upstream effector of ROCK1/F-actin.…”
Section: Discussionsupporting
confidence: 55%
“…Our previous study [7] reported that F-actin and lamellipodium are vital for cancer mobilization. At the molecular level, F-actin multimerizes at the membrane and then forms the lamellipodium, which induces cellular deformation and migration [51]. In this study, immunofluorescence was used to observe alterations in the lamellipodium.…”
Section: F-actin/lamellipodium Signaling Pathway Is Impaired Bymentioning
confidence: 99%
“…[17,18] Compared with normal cells, cancer cells have faster growth and invasive capabilities and require mitochondria to provide more energy. [19] Mitochondrial dysfunction is one of the signs of apoptosis induced by intrinsic pathway. [20] Mitochondria plays an important role in the regulation of apoptosis signals.…”
Section: Discussionmentioning
confidence: 99%